2012
DOI: 10.1017/s0021932012000211
|View full text |Cite
|
Sign up to set email alerts
|

Health Inequalities Among Urban Children in India: A Comparative Assessment of Empowered Action Group (Eag) and South Indian States

Abstract: As India rapidly urbanizes, within urban areas socioeconomic disparities are rising and health inequality among urban children is an emerging challenge. This paper assesses the relative contribution of socioeconomic factors to child health inequalities between the less developed Empowered Action Group (EAG) states and more developed South Indian states in urban India using data from the 2005-06 National Family Health Survey. Focusing on urban health from varying regional and developmental contexts, socioeconom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 18 publications
1
43
0
Order By: Relevance
“…An ecological study using data from the Indian National Family Health Survey showed that the children in the lowest wealth quartile in urban areas have significantly lower coverage (around 40%) than in any other urban wealth group [38]. Another study examined the survey data in more detail to compare a wider range of SE factors and outcomes of 1877 children in less developed Empowered Action Group states with more developed northern counterparts and found that having an illiterate mother or father, poverty, and being a 3rd born child or greater had the greatest effect on immunization coverage [46]. However, studies conducted in individual locations paint a more heterogeneous picture.…”
Section: Resultsmentioning
confidence: 99%
“…An ecological study using data from the Indian National Family Health Survey showed that the children in the lowest wealth quartile in urban areas have significantly lower coverage (around 40%) than in any other urban wealth group [38]. Another study examined the survey data in more detail to compare a wider range of SE factors and outcomes of 1877 children in less developed Empowered Action Group states with more developed northern counterparts and found that having an illiterate mother or father, poverty, and being a 3rd born child or greater had the greatest effect on immunization coverage [46]. However, studies conducted in individual locations paint a more heterogeneous picture.…”
Section: Resultsmentioning
confidence: 99%
“…& Religion: Muslim(1)/others (0) The information collected on eight categories of religion was grouped into three categories (Hindu/Muslim/Others) in the bivariate analyses and two categories (Muslim/ Others) in the decomposition analyses. A number of studies have established that Muslims are in disadvantageous position not only in socioeconomic terms but also in terms of public health indicators as well (e.g., Basant 2007;Arokiasamy et al 2012;Jain et al 2012;IIPS andMacro International 1992-2006;Government of India 2006). & Caste: Scheduled Castes/Scheduled Tribes(1)/others (0) The caste system is a type of social institution in India where social stratification of communities is defined by several endogamous inherited groups called Jatis.…”
Section: Socioeconomic Variables/independent Variablesmentioning
confidence: 99%
“…In India, the issue of socioeconomic inequalities in health has been largely discussed in the context of women and children Arokiasamy et al 2012;. Despite India having the second largest older population in the world in terms of absolute numbers, the association between socioeconomic inequality and health among the older population remains poorly understood (National Research Council of the National Academies 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have examined the inequality in childhood undernutrition and found that the economic status of households is the prime contributor in explaining the inequality in childhood undernutrition in urban India [21], [22]. A few studies have also highlighted the growing poor/non-poor gap in the utilization of maternal healthcare services and child health in urban India [23], [24].…”
Section: Introductionmentioning
confidence: 99%